كشف الوجوه البيانية في قصيدة الشيخ علي الصابوني للحبيب أبي بكر العدني - Huda, Nailil; Prasetyo, Rizal; Lintang, Daud (Ta'limi | Journal of Arabic Education and Arabic Studies, 2022)
This research aims to unmask the beauty of the Arabic language as well as to reveal the shape of the parrot contained in the qasidah mirṡāh by Habib Abu bakr al-'Adni. As for the problem in this discussion, First: who is shaykh 'ali al-ṣābūnī?  Second: who is Habib Abu Bakr al-'adni?  Third: what is the shape of the parrot in the qasidah mirṡāh by Habib abu bakr al-'adni?  Fourth: what is the meaning of the lamentation qasidah in habib abu bakr al-'adni's qasidah mirṡāh? In this study the author used the library method by reading, analyzing and collecting data by referring to sources, references and books related to this theme. Then, for the stages of his research is to  collect poems that contain only parrots and look for bayan elements, include the meaning of the poem in language and overall meaning, and reveal the parrot forms contained in the poem. The results of this study contained 1 tasybîh and 17 majãz. In addition, this study became a picture of the breadth of language science, especially arabic science. Because, the style (uslub) of language communication is certainly very influential on all areas of europeanism and Arabic literature.